Function of the RNA-targeting class 2 type VI CRISPR Cas system of Rhodobacter capsulatus - Kretz, Jonas; Börner, Janek; Friedrich, Tobias; McIntosh, Matthew; Procida-Kowalski, Tara; Gerken, Florian; Wilhelm, Jochen; Klug, Gabriele (Frontiers in Microbiology, 2024)
Bacteria use CRISPR Cas systems to defend against invading foreign nucleic acids e.g. phage genomes, plasmids or mobile genetic elements. Some CRISPR Cas systems were reported to have physiological importance under a variety of abiotic stress conditions. We used physiological tests under different stress conditions and RNA-seq analyses to address the possible function of the RNA-targeting class 2 type VI CRISPR Cas system of the facultative phototrophic α-proteobacterium Rhodobacter capsulatus. Expression of the system was low under exponential non-stress conditions and high during oxidative stress, membrane stress and in stationary phase. Induction of the CRISPR Cas system in presence of a target protospacer RNA resulted in a growth arrest of R. capsulatus. RNA-seq revealed a strong alteration of the R. capsulatus transcriptome when cas13a was induced in presence of a target protospacer. RNA 5′ end mapping indicated that the CRISPR Cas-dependent transcriptome remodeling is accompanied by fragmentation of cellular RNAs, e.g. for mRNAs originating from a genomic locus which encodes multiple ribosomal proteins and the RNA polymerase subunits RpoA, RpoB and RpoC. The data suggest a function of this CRISPR Cas system in regulated growth arrest, which may prevent the spread of phages within the population.